Prognostic value of tumor length in predicting survival for patients with esophageal cancer - Wang, Haijing; Bi, Liangwen; Zhang, Lizhen; Zhao, Weiyong; Yang, Min; Sun, Xinchen (Translational Cancer Research; Vol 7, No 3 (June 27, 2018): Translational Cancer Research, 2018)
Background: To determine the prognostic value of tumor length in predicting overall survival (OS) for patients with esophageal cancer. Methods: Patients who were diagnosed with esophageal cancer between 2010 and 2014 were identified from the Surveillance Epidemiology and End Results (SEER) data. We performed Kaplan-Meier survival analysis and developed a Cox regression proportional hazard model to explore the effect of tumor length on survival. Results: A total of 6,897 esophageal cancer patients were identified. The patients were classified according to tumor length: 2,334 patients had a tumor length ≤3 cm, and 4,563 patients had a tumor length >3 cm. Patients with a tumor length >3 cm were more likely to have poorer histological grade (P